Enzyme-Linked Immunosorbent Assay For The Detection Of Alloantibodies To Factor IX In Hemophilia B - Örstavik, K H; Örstavik, I (Thrombosis and Haemostasis, 1981)
A solid phase enzyme-linked immunosorbent assay (ELISA) was developed for the detection and quantitative determination of acquired inhibitors to factor IX. Wells of polystyren Micro-ELISA plates were coated with the IgG fraction of a sheep antiserum to human factor IX. After incubation with pooled normal plasma as a factor IX source, the wells were incubated with test plasma. The binding of alloantibodies to the factor IX-sheep-anti-factor IX complexes was then detected by incubation with alkaline phophatase conjugated antiserum to human IgG. As substrate was used p-nitrophenyl phosphate.Plasma samples from five patients with severe hemophilia B and acquired inhibitors to factor IX were examined. All samples gave a positive reaction in the ELISA. The titers as determined in the ELISA were in good agreement with the titers as determined in a coagulation assay (0.1-800 U/ml). Plasma from 13 patients with hemophilia B and no detectable inhibitor in a coagulation assay all gave a negative reaction in the ELISA. A negative reaction was also found in plasma from four patients with hemophilia A and acquired inhibitors to factor VIII, and in plasma from 15 healthy persons.It is concluded that the ELISA is a simple and sensitive technique for the determination of acquired inhibitors to factor IX in hemophilia B.